2016
DOI: 10.1016/j.gene.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

PELP1: Structure, biological function and clinical significance

Abstract: Proline-, glutamic acid-, and leucine-rich protein 1 (PELP1) is a scaffolding protein that functions as a coregulator of several transcription factors and nuclear receptors. Notably, the PELP1 protein has a histone-binding domain, recognizes histone modifications and interacts with several chromatin-modifying complexes. PELP1 serves as a substrate of multitude of kinases, and phosphorylation regulates its functions in various complexes. Further, PELP1 plays essential roles in several pathways including hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 74 publications
(115 reference statements)
1
57
0
Order By: Relevance
“…PELP1 functions are vital in oncogenic processes, such as cell cycle, survival, metastasis, hormone therapy resistance, and autophagy . Several reports have shown that PELP1 downregulation significantly reduced the proliferation, survival, migration, and invasion of cancer cells in multiple cancer types .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PELP1 functions are vital in oncogenic processes, such as cell cycle, survival, metastasis, hormone therapy resistance, and autophagy . Several reports have shown that PELP1 downregulation significantly reduced the proliferation, survival, migration, and invasion of cancer cells in multiple cancer types .…”
Section: Discussionmentioning
confidence: 99%
“…Proline‐, glutamic acid‐, and leucine‐rich protein 1 (PELP1) is a scaffolding protein that regulates several signaling pathways and many biological processes . Structurally, PELP1 has 10 nuclear receptors (NRs) interacting boxes LXXLL motifs that facilitate its interaction with NRs, proline‐rich motifs that facilitate interactions with SRC homology 3 domain‐containing proteins, and C‐terminus glutamic acid‐containing region which assists in interactions with histone proteins .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PELP1 is expressed in a variety of tissues, with highest expression in the brain, ovaries, testes, and uterus [1620]. In addition, PELP1 exhibits both nuclear and cytoplasmic localization [20], and phosphorylation of PELP1 can control its localization, interaction with other proteins, and stability in cells [16, 17]. To understand its importance in E2 actions in the brain, our group recently created a PELP1 forebrain-specific knockout (PELP1 FBKO) mouse model [16].…”
Section: Introductionmentioning
confidence: 99%